Inhibition of inward rectifier potassium currents by chloroquine causes significant electrophysiological changes in the rat thoracic veins myocardium - A.D. Ivanova; V.S. Kuzmin (Учёные записки Казанского университета: Серия Естественные науки, 2018)
Thoracic (caval and pulmonary) vein myocardial tissue is considered as a source of ectopic activity capable of initiating atrial fibrillation. The reasons which underline thoracic vein proarrhythmicity may be related to the expression level of the inward rectifier potassium current (IK1) critical for stable resting membrane potential (RMP) maintenance. In the present study the effect of IK1 inhibition by chloroquine (5 ?M) on the membrane resting and action potentials (AP) were recorded in the superior caval, pulmonary veins and left atria tissue preparations. There were no differences in RMP level: the AP duration in veins was significantly longer than in the atrium under control conditions. The chloroquine application increased the AP duration greater in the vein myocardium as compared to the left atrium. The study results allow to suggest that the thoracic vein myocardium has a lower density of IK1 current relatively to the working atrial myocardium.